DETERMINAN KEJADIAN DIARE PADA ANAK BALITA DI KELURAHAN SEKARJAYA UPTD PUSKESMAS SEKARJAYA KABUPATEN OKU - Sarwoko S, Sabtian; Marita, Yulis; Joni Yansyah, Eka (LPPM STIKes Mitra Adiguna, 2025)
One of the causes of increasing incidence of disease and death in children under five is diarrhea. Most diarrhea is caused by contaminated drinking water and food consumed. This study used Cross Sectional, with the population being toddlers in Sekarjaya Village, namely 152 toddlers and a sample size of 110 samples was obtained. Univariate analysis showed that out of 110 respondents, 41 (37.3%) toddlers had poor maternal knowledge, and 69 (62.7%) had good maternal knowledge. The water quality that did not meet the physical water quality standards was 33 (30.0%) and the physical water quality met the physical water quality standards was 77 (70.0%). Poor hand washing habits were 37 (33.6%) and good hand washing habits were 73 (66.4%). From the Bivariate Analysis, the results showed that there was a relationship between maternal knowledge, physical quality of water, hand washing with the incidence of diarrhea in toddlers with p values ??of 0.004, 0.001 and 0.000.The conclusion of this study is that there is a relationship between maternal knowledge, physical quality of water and hand washing with the incidence of diarrhea in toddlers. Suggestions for health workers to be more active in educating the public about preventing diarrheal diseases, and water quality that meets standards for consumption and how to wash hands properly.